Distributed control of mobile robots in an environment with static obstacles. Issue 2 (12th May 2021) - Giannousakis, Konstantinos; Tzes, Anthony
Abstract: This study addresses the problem of deploying a group of mobile robots over a non‐convex region with obstacles. Assuming that the robots are equipped with omnidirectional range sensors of common radius, disjoint subsets of the sensed area are assigned to the robots. These proximity‐based subsets are calculated using the visibility notion, where the cell of each robot is treated as an opaque obstacle for the other robots. Based on that, optimal spatially distributed coordination algorithms are derived for the area coverage problem and for the homing problem, where the swarm needs to move to specific locations. Experimental studies demonstrate the results.